ECOLOGICAL DEVELOPMENT OF DOMESTIC ENTREPRENEURSHIP IN MODERN TURBULENT CONDITIONS - SHABANOV, Ruslan Mustafa Ogly (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Today, ecology plays an important role in the life of most spheres. Obviously, economic development is associated with environmental changes. In recent years, the Earth’s ecological system has undergone a significant decline. Due to the unsustainable use of natural resources without further restoration, the efficiency of ecosystems is being impaired. The functionality of ecosystems has a direct impact on people’s living standards and well-being. Environmental changes are mostly caused by the rapid economic development in most countries of the world. The needs of the population are growing every year, and the amount of natural resources is decreasing, so it is important to establish the relationship between the social, economic and natural environments. Ukraine, like many other countries, faces the need to combine economic growth and environmental protection. Therefore, the analysis of the environmental development of domestic business is extremely important for understanding current trends, identifying problematic aspects and developing effective strategies for sustainable development. In the current context of global environmental challenges, Ukrainian enterprises are increasingly realizing the importance of transition to sustainable development. The environmental development of enterprises is not only a requirement of the times, but also a strategic necessity, which implies a systematic improvement of economic activity taking into account environmental factors. The main goal of this process is to harmonize economic growth with minimal negative impact on the environment. Ecological entrepreneurship plays an important role in this process, covering both the production of environmentally friendly products and the introduction of resource-saving technologies, the use of recycled materials, the development of organic farming and alternative energy. Environmental control plays an important role in the government’s policy, as it is aimed at ensuring compliance with legal regulations and promoting environmental responsibility of businesses. The effectiveness of control depends on a harmonious combination of legislative, economic, administrative and organizational instruments. In particular, the legislative framework regulates the requirements for environmental activities, economic levers form a system of incentives and sanctions, administrative levers ensure enforcement of regulations, and organizational levers create conditions for interaction between the state, business and the public. Together, they form a system that ensures not only control but also the development of environmental responsibility of enterprises. At the same time, despite the existence of a regulatory framework and control tools, the current state of environmental entrepreneurship in Ukraine remains ambiguous. Significant barriers include a lack of funding, outdated technologies, low environmental awareness among entrepreneurs, and insufficient government support. Therefore, the prospects for the development of environmental entrepreneurship directly depend on strengthening government policy, investing in innovation, and creating a culture of sustainable development among both businesses and consumers. In the context of European integration, the intensification of environmental entrepreneurship can become not only a means of environmental protection, but also a competitive advantage in the international market. Thus, the environmental development of enterprises in Ukraine is a key factor in sustainable economic growth and environmental protection. Its effective implementation requires not only controlling and legislative mechanisms, but also active participation of business, investments in eco-technologies and the formation of an environmental culture. Only with a comprehensive approach will environmental entrepreneurship become a real competitive advantage of Ukraine on the world stage.